RETENÇÃO DE ÁGUA E DISTRIBUIÇÃO DE TAMANHO DE POROS EM SOLOS CULTIVADOS COM CANA-DE-AÇÚCAR EM COMPARAÇÃO COM ÁREA DE PRESERVAÇÃO PERMANENTE - Coutinho, Edilson Amaral Tavares; Silva, Alison José da; Cavalcante, Douglas Monteiro; Almeida, Brivaldo Gomes de; Ribeiro Filho, Mateus Rosas; Almeida, Ceres Duarte Guedes Cabral de (IRRIGA, 2023)
WATER RETENTION AND PORE SIZE DISTRIBUTION IN SOILS CULTIVATED WITH SUGARCANE COMPARED TO A PERMANENT PRESERVATION AREA1 EDILSON AMARAL TAVARES COUTINHO2; ALISON JOSÉ DA SILVA2; DOUGLAS MONTEIRO CAVALCANTE2; BRIVALDO GOMES DE ALMEIDA2; MATEUS ROSAS RIBEIRO FILHO2 AND CERES DUARTE GUEDES CABRAL DE ALMEIDA3 1Part of the first author’s dissertation of Master of Science presented at the Soil Science Post-Graduation Program at the Federal Rural University of Pernambuco (UFRPE) 2Agronomy Departament, Soil Science Post-Graduation Program at the Federal Rural University of Pernambuco (UFRPE), St Dom Manuel de Medeiros, s/n, Dois Irmãos, CEP 52171-900, Recife, PE, Brazil. Fone (81) 999077045, email: edilsonsta@gmail.com, alisonjose1997@gmail.com, cavalcante.doug@gmail.com, brivaldo.almeida@ufrpe.br, mateus.ribeirofo@ufrpe.br 3Full Professor, Agricultural College Dom Agostinho Ikas, CODAI, UFRPE, Rodovia PE 005, km 25, 4000, Tiuma, CEP 54737-200, São Lourenço da Mata, PE, Brazil, ceres.cabral@ufrpe.br 1 ABSTRACT The soil structural condition, cultivated with sugarcane, is related to the type of harvest adopted which influences the soil porosity, an important variable in the circulation of the liquid and gaseous phases of the soil. These phases can be directly affected by soil management and cultivation, where mechanized raw sugarcane harvesting can improve them. Thus, this research aimed to evaluate soil porosity (P) and its pore size distribution (PSD) in classes, as well as the soil water content at field capacity (qfc), cultivated with sugarcane under two harvest methods: raw and burnt sugarcane. Thus, three areas were compared: two under different ways of harvesting sugarcane (with and without burning); and one in a native forest as a reference. P, PSD (macro, meso, and microporosity), and qfc were determined in soil samples collected in volumetric cylinders, by the saturation and tension table methods, respectively. The results point out that the soil under native forest presented the highest values for the evaluated attributes, indicating that sugarcane cultivation, with or without burning, reduces them. Burning promoted negative changes in the soil concerning water conduction and soil aeration, even in a recent cultivation area (five years), promoted by the reduction of qfc (-62.09%), mainly reflecting the decrease in macroporosity (-31.73%) and microporosity (-24.48%). Keywords: burned sugarcane, raw sugarcane, sandy soil, field capacity, native forest. COUTINHO, E. A. T.; SILVA, A. J.; CAVALCANTE, D. M.; ALMEIDA, B. G.; RIBEIRO FILHO, M. R.; ALMEIDA. C. D. G. C. RETENÇÃO DE ÁGUA E DISTRIBUIÇÃO DE TAMANHO DE POROS EM SOLOS CULTIVADOS COM CANA-DE-AÇÚCAR EM COMPARAÇÃO COM ÁREA DE PRESERVAÇÃO PERMANENTE 2 RESUMO A condição estrutural do solo, cultivado com cana-de-açúcar, está relacionada com o tipo de colheita adotado, o qual influencia a porosidade do solo, uma importante variável de circulação das fases líquida e gasosa do solo. Estas fases podem ser afetadas diretamente pelo manejo e cultivo do solo, onde a colheita mecanizada da cana-de-açúcar crua pode melhorá-las. Assim, esta pesquisa objetivou avaliar a porosidade do solo (P) e sua distribuição de tamanho de poros (PSD), bem como o conteúdo de água na capacidade de campo (qfc) do solo cultivado com cana-de-açúcar sob dois métodos de colheita: crua e queimada. Desse modo, foram comparadas três áreas: duas sob diferentes formas de colheita de cana (com e sem queima); e uma em mata nativa, como referência. A P, PSD (macro, meso e microporosidade) e qfc foram determinadas nas amostras coletadas em cilindros volumétricos, utilizando-se os métodos da saturação e da mesa de tensão, respectivamente. Os resultados comprovam que o solo sob mata nativa apresentou os maiores valores para os atributos avaliados, comprovando que o cultivo da cana-de-açúcar, com ou sem queima, reduz os valores desses atributos. A queima promoveu mudanças negativas no solo em relação à condução hídrica e aeração do solo, mesmo em área de cultivo recente (cinco anos), promovidas pela redução da qfc (-62,09%), refletindo, principalmente na diminuição da macroporosidade (-31,73%) e microporosidade (-24,48%). Palavras-chave: cana queimada, cana crua, solo arenoso, capacidade de campo, floresta nativa.